UPAYA MENINGKATKAN HASIL BELAJAR MATA PELAJARAN ILMU PENGETAHUAN SOSIAL PADA KONSEP KENAMPAKAN ALAM MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE LEARNING JIGSAW DI KELAS 3 SDN KUBANG KEMIRI - Ahmad Mubarok (Jurnal Anak Bangsa, 2023)
This research is a Classroom Action Research, carried out collaboratively between researchers, observers, and the subjects studied. The purpose of this study was to improve social studies learning outcomes for third grade students through the application of the jigsaw learning model. The subjects of this study were 35 students of class III at SDN Kubang Kemiri. This research was conducted in two cycles. Each cycle consists of four main actions, namely planning, implementing, observing and reflecting. And held two meetings each cycle. At the end of each cycle a test is held using the question instrument. The results showed that there was an increase in the acquisition of the average student score, namely the first cycle obtained a value of .65, and the second cycle 75. Likewise, from the results of observations of student activity there was an increase. The first cycle is 17, and the second cycle is 22. This study concludes that the application of the jigsaw learning model can improve student learning outcomes in Social Science Subject Subject Natural Appearance Class III SDN Kubang Kemiri. In addition, this learning model also increases student participation and learning activities in the learning process